Estudo do processo de obtenção de filmes espessos autossustentados porosos por meio de sinterização seletiva a laser - Mendes, Flávia Bueno (2023)
BaTiO3 is an ABO3-type perovskite with tetragonal structure at room temperature and is also known for its excellent dielectric, ferroelectric and piezoelectric properties and is used in dielectric capacitors, sensors, actuators and sound detectors. The performance of these components, as well as that of any ceramic component, is strongly influenced by the characteristics of the precursors used and the processing route chosen. The preparation of materials by new routes can lead to the discovery of distinct morphological characteristics, and change the properties of these materials. A route that has been widely used in ceramic processing is known as Additive Manufacturing, which covers technologies that allow the creation of objects from a virtual model. One such technology is the selective laser sintering method - SLS, where a CO2 laser will irradiate the sample, producing surface heating in a time interval of a few seconds, making it possible to obtain bodies with different properties from those sintered by conventional methods. Ceramic materials, due to their low resistance to thermal shock, are sintered through indirect selective laser sintering - iSLS, where the ceramic material is mixed with a polymer that will melt during the process and bind the ceramic particles. The objective of this work is to study the parameters of the preparation process of porous ceramics by indirect selective laser sintering to obtain self-sustained thick films of pure BaTiO3. Also in this context, the results of computer simulations on the temperature distribution on the surface of the powder bed will also be presented during the iSLS process. Such study encompassed the elaboration of a three-dimensional mathematical model for the problem, the solution of the model through the Finite Element Method using the COMSOL Multiphysics software, and the validation of the results by comparing the results obtained with data generated in experimental work.